Spring and autumn fauna of Cladocera (Crustacea: Branchiopoda) in the center of East Asia plain: Hunan and Hubei Provinces of China - Dadykin, Ivan A.; Sinev, Artem Y.; Gu, Yangliang; Han, Bo-Ping (Zootaxa, 2023)
Cladoceran (Crustacea: Branchiopoda) fauna of Hunan and Hubei provinces of China was studied in April 2014 and October 2018. 49 species of Cladocera were found, Anthalona sanoamuangae Sinev & Kotov, 2012 was recorded for China for the first time. Eight species were newly recorded for central China, taxonomic status of four species was clarified. Among the observed species, 19 taxa are predominantly Boreal, 13 species are recorded predominantly in south part of temperate zone and subtropics, and 17 species are mainly tropical. Significant difference was revealed between the spring and autumn fauna: Boreal species were the most frequent in spring, whereas subtropical and tropical species became more common in autumn. Species diversity and composition of the cladoceran fauna in the center of East Asia plain is discussed.